Effect of Biodigester Effluent on Carbohydrate Metabolizing Enzymes and Oxidative Stress Markers in the African Catfish (Clarias gariepinus) - (:unkn) unknown (My University, 2024)
Background: Although the use of biodigester effluent as fish feed have been previously reported, however, its effect on the metabolic activities of fish, which might inform its safety and administration guideline in fish farming is poorly understood. Aim: The aim of the present study was to investigate the effects of pig dung biodigester effluent (PDBE) on key metabolic enzymes and antioxidant markers in Clarias gariepinus. Methodology: Fifteen catfish (120±10 g) were purchased and grouped into three. Group I (control): exposed to freshwater; group two: exposed to raw PDBE; and group three: exposed to 1:10 dilution of PDBE. After exposure, serum lactate dehydrogenase (LDH) and glucose-6-phosphate dehydrogenase (G-6-PDH) activities and total protein concentration were measured using commercially available kits while serum reduced glutathione concentration and glutathione peroxidase activity were measured using standard methods. Results: The TP (g/dl) for control, group II and III were 6.00±0.12; 20.0±0.10 and 6.86±0.02 respectively, while their LDH activities (IU/L/min) were 115.00±1.57; 422.00±5.64 and 105.00±5.18 respectively. The activities of G-6-PDH (U/L/min) in control, group II and III were 8.00±0.40; 32.00±0.73; 7.00±0.40 respectively, while their glutathione concentrations (µg/ml) were 6.5±0.01; 0.5±0.01 and 9.83±0.12 respectively. The activities of GPx (µg/ml/min) in control, group II and III were 15±0.25; 64±1.99 and 10±1.33. Conclusion: Raw PDBE caused a significant alteration in the metabolic parameters of catfish however these alterations were absent in a 1:10 dilution of the PDBE. This study’s novel inclusion of both raw and diluted PDB effluent exposures offers valuable guidelines for effluent usage in aquaculture.
Keywords: African Research